Fetal surgery for spina bifida aperta. Issue 6 (13th July 2018) - Joyeux, Luc; Danzer, Enrico; Flake, Alan W; Deprest, Jan
Abstract : Spina bifida aperta (SBA) is one of the most common congenital malformations. It can cause severe lifelong physical and neurodevelopmental disabilities. Experimental and clinical studies have shown that the neurological deficits associated with SBA are not simply caused by incomplete neurulation at the level of the lesion. Additional damage is caused by prolonged exposure of the spinal cord and nerves to the intrauterine environment and a suction gradient due to cerebrospinal fluid leakage, leading to progressive downward displacement of the hindbrain. This natural history can be reversed by prenatal repair. A randomised controlled trial demonstrated that mid-gestational maternal-fetal surgery for SBA decreases the need for ventriculoperitoneal shunting and hindbrain herniation at 12 months and improves neurological motor function at 30 months of age. This came at the price of maternal and fetal risks, the most relevant ones being increased prematurity and a persistent uterine corporeal scar. Recently minimally invasive fetal approaches have been introduced clinically yet they lack extensive experimental or clinical trials. We aim to provide clinicians with the essential information necessary to counsel SBA parents as the basis for considering referral of selected patients to expert fetal surgery centres. We review the reported clinical outcomes and discuss recent developments of potentially less invasive fetal SBA approaches.